ANALISIS HUKUM KONSUMSI KHAMR DAN DAMPAK TERHADAP KESEHATAN MANUSIA DALAM PERSPEKTIF FIQIH JINAYAH DAN MAQĀṢID AL-SYARĪʿAH - Azhara, Siti; Hafdhah Fajrillah, Ulya; Husna, Lailan; Sari Dauly, Shintia; Gaffar Harahap, Abidin (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2025)
: Legal analysis regarding the consumption of khamr and its impact on human health from the perspective of Islamic criminal law (Fiqh Jinayah) and the objectives of sharia (Maqāṣid al-Syarīʿah) shows that khamr, which includes all intoxicating substances, is prohibited because it damages the mind and body. This prohibition, which was first found in QS. An-Nahl (16): 67 and QS. Al-Baqarah (2): 219, further clarified through QS. An-Nisa (4): 43 which prohibits the consumption of khamr during prayer, until it is finally confirmed in the QS. Al-Maidah (5): 90-91 as an act of Satan that destroys happiness. Legal sanctions against khamr consumption do not only take the form of flogging, but also include social, medical and psychological rehabilitation approaches, reflecting sharia wisdom in protecting the mind, body and social life. The aim of sharia is to maintain human physical and mental safety, as well as comprehensive social welfare.